The adjacency-pell-circulant sequences - Aküzüm, Yesim; Deveci, Ömür; Artun, Gizem (Utilitas Mathematica, 2019)
Ill this work, we define the generalized adjacency-Pell-circulant sequences by using the circulant matrix which is obtained from the characteristic polynomials of the adjaceucy-Pell sequences. Also, we derive the adjacency-Pell-circulant sequences by the aid of the generalized adjaceucy-Pell-circulant sequences. Then we give some properties of these sequences such as the generating matrix, the Binet formula, the generating function, the exponential representation. © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.